SYNTHESIS OF THIOMETHYLATED CALIX[4]RESORCINARENE BASED ON FENNEL OIL VIA CHLOROMETHYLATION - Suryadi Budi Utomo; Jumina Jumina; Dwi Siswanta; Mustofa Mustofa; Naresh Kumar (Universitas Gadjah Mada, 2011)
A research has been conducted to synthesize thiomethylated-C-4-methoxyphenylcalix[4]resorcinarene using fennel oil as a starting material. The synthesis was carried out in four steps i.e. (1) oxidation of anethole to yield p-anisaldehyde, (2) HCl-catalyzed condensation of p-anisaldehyde with resorcinol, (3) chloromethylation of C-4-methoxyphenylcalix[4]resorcinarene with paraformaldehyde and HCl in the presence of ZnCl2 to yield tetrakis-chloromethyl-C-4-methoxyphenylcalix[4]resorcinarene, and (4) reaction of tetrakis-chloromethyl-C-4-methoxyphenylcalix[4]resorcinarene with thiourea followed by hydrolysis with sodium hydroxide solution to yield tetrakis-thiomethyl-C-4-methoxyphenylcalix[4]resorcinarene. The prepared compounds were characterized based on melting point, FT-IR, and NMR spectrometers. According to the analysis of 1H-NMR spectrometer, C-4-methoxyphenylcalix[4]resorcinarene and tetrakis-chloromethyl-C-4-methoxyphenylcalix[4]resorcinarene were observed in the chair or flattened partial cone conformation, while tetrakis-thiomethyl-C-4-methoxyphenylcalix[4]resorcinarene tend to exist in the crown or cone conformation.